The Role of Organizational Commitment and Organizational Culture in Promoting Knowledge Sharing (Case Study on Employees of KSP CU Tilung Jaya Putussibau) - Triadi*, Masius; Fauzan, Rizky (Riwayat: Educational Journal of History and Humanities, 2023)
Abstract: In the era of globalization and rapid technological advancements, an organization's ability to manage and share knowledge becomes crucial for remaining competitive and innovative. The purpose of this research is to investigate the extent to which organizational commitment and organizational culture influence knowledge sharing among employees at the Koperasi Simpan Pinjam (KSP) CU Tilung Jaya. Organizational commitment, encompassing affective, continuance, and normative commitments, was studied as a factor influencing knowledge sharing. Organizational culture, with indicators including innovation, result orientation, employee orientation, aggressiveness, and stability, was also identified as a factor affecting knowledge sharing behavior. This study adopted a survey approach using a questionnaire as the data collection instrument, distributed to 50 respondents out of 115 employees of KSP CU Tilung Jaya. Data analysis was conducted using multiple linear regression with SPSS version 25. The findings reveal that both organizational commitment and organizational culture have a positive impact on knowledge sharing practices. This research provides further insights into how internal organizational factors, like organizational commitment and culture, can influence knowledge sharing behavior. These findings can serve as a foundation for the administrators of KSP CU Tilung Jaya to formulate policies that support and encourage knowledge sharing within the organization